KEMAMPUAN BERPIKIR KRITIS MATEMATIS DAN SELF CONFIDENCE SISWA SMP MELALUI PENDEKATAN REALISTIC MATHEMATIC EDUCATION - Delina Delina; M Afrilianto; Euis Eti Rohaeti (IKIP Siliwangi, 2018)
This research aims to examine of mathematical critical thinking ability of mathematic and self confidence of students who get Realistic Mathematic Education approach compared to those who get ordinary learning. The method used in this research is the experimental method. The population in this study were junior high school students in Purwakarta, while the sample was SMP Negeri 1 Plered and selected two classes randomly from all of the existing VII class. Then from the two classes are assigned randomly into the experimental class and control class. The experimental class received learning with Realistic Mathematic Education approach and control class gained regular learning. The instrument used is the test of critical thinking ability mathematically and scale self confidence. From the calculation and hypothesis test concluded that the improvement of critical thinking ability of mathematic and self confidence of students who get Realistic Mathematic Education approach is better than those who get regular learning.